Estratégias bioclimáticas passivas para autoconstrução em Santa Maria - RS - Brum, Graziane da Silva (2024)
This study addresses the theme of passive bioclimatic strategies in self-built housing, with a focus on Santa Maria, RS. In view of the inadequacy of public housing policies to serve the low-income population and the prevalence of self-construction as a viable alternative, this research seeks to propose accessible and low-cost solutions to improve the thermal comfort and energy efficiency of these dwellings through passive bioclimatic strategies. To achieve this purpose, a methodology was adopted that combined bibliographic research, exploratory and qualitative analysis. Four self-built houses in different communities of the city were selected for analysis. Data collection involved techniques such as in situ observation and interviews with occupants, as well as a survey of the costs of construction materials for local context, which made it possible to identify the specific needs of each house and propose targeted interventions. From there, solutions based on bioclimatic strategies were proposed to make the houses more suitable for the occupants’ thermal comfort, as well as to improve their energy efficiency applicable in social housing in general. Finally, a technical guidebook was prepared aimed at self-built housing, where bioclimatic strategies are presented through a language accessible to the low-income people, as well as collaborating with professionals who work in the area of HIS. This research contributes to a better understanding of the context of self-built housing, as well as to the dissemination of bioclimatic strategies and their cost to the context of Santa Maria.